Variations in perceived stress among Syrian refugee parents resettled through different sponsorship programs in Canada - Yasma Ali-Hassan; Kamyar Sartipi; Ali Jammal; Durdana Khan; Hala Tamim (Elsevier, 2021)
Background: Little is known about the perceived stress level of Syrian Refugee (SR) parents residing in Canada specifically in relation to different sponsorship programs. This study aims to assess the relationship between the different sponsorship programs [Government-Assisted Refugees (GAR), Privately Sponsored Refugees (PSR) and Blended Visa Office-Referred refugees (BVOR)] and perceived stress among SR parents, with at least one child under the age of four, who resettled in the Greater Toronto area after 2015. Methods: A convenience sample of 155 Syrian Refugee (SR) parents was recruited. Perceived levels of stress were measured using the Perceived Stress Scale (PSS-10). Multiple linear regression analysis was performed to assess the independent relation between several types of sponsorship programs and PSS adjusting for demographic, economic and social factors. Results: The overall average PSS score was found to be 12.5 ± 7.2 with BVORs presenting the highest level of moderate stress when compared to GARs and PSRs (75.0% compared to 39.5% and 35.2% respectively). Multivariate analysis showed that the mean PSS was significantly higher among BVORs when compared with GARs (Adj β = 4.8; 95% CI 0.4, 9.2). No significant difference in PSS levels was reported when PSRs were compered to GARs. Increased PSS scores were found to be associated with worse family functioning (Adj β = 4.2; 95% CI 1.0, 7.4), while decreased PSS scores were associated with increased age (Adj β = -0.4; 95% CI -0.6, -0.1). Conclusion: A better understanding of the various underlying factors associated with elevated stress is essential for improving the quality of life for SRs in Canada. Results of the study may help tailor more effective preventative measures or government interventions dedicated to reducing stress levels among this population.